2007
DOI: 10.1159/000102162
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Necrosis Factor Polymorphisms with Guillain-Barré Syndrome

Abstract: It has been reported that the tumor necrosis factor (TNF)α promoter polymorphism is associated with autoimmune disease and inflammatory disease. It has also been claimed that this polymorphism may affect TNFα expression. We investigated the TNFα –308 polymorphism and TNFα levels in 79 unrelated Chinese patients with Guillain-Barré syndrome (GBS) and 78 healthy controls using PCR-RFLP and ELISA assay. Patients with GBS were divided into 2 subgroups, acute inflammatory demyelinating polyradiculoneuropathy (AIDP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…TNF-α is able to inhibit Schwann cell proliferation and mediate Schwann cell death (27). TNF-α was elevated and associated with disease severity in EAN (28) and GBS (29). In a further study, Zhang et al (30) observed that the onset of EAN in TNF-α gene-deficient mice was markedly later than that in wild type mice.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is able to inhibit Schwann cell proliferation and mediate Schwann cell death (27). TNF-α was elevated and associated with disease severity in EAN (28) and GBS (29). In a further study, Zhang et al (30) observed that the onset of EAN in TNF-α gene-deficient mice was markedly later than that in wild type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Association between different HLA types and GBS has been reported with preceding C. jejuni infection but has only been observed in some populations (9 -12). Polymorphisms in the TNF gene have been associated with a rare GBS subtype in a Chinese population (13), but association studies have so far failed in identifying single genes regulating the more prevalent AIDP subtype. This indicates a genetically complex regulation of GBS, and large homogeneous patient cohorts are required for accurate genetic analysis.…”
Section: G Uillain-barré Syndrome (Gbs)mentioning
confidence: 99%
“…In addition, increased proinfl ammatory cytokine levels were also found in noninfl ammatory neuropathies [ 18 , 19 ]. A link was suggested between polymorphisms in the gene of the proinfl ammatory cytokine tumor necrosis factor (TNF)-α and the occurrence of GBS [ 20 ]. There are further reports that modulation of the innate cytokine system by application of cytokines or cytokine inhibitors may cause neuropathies [ 21 , 22 ].…”
Section: Cytokines In Peripheral Neuropathiesmentioning
confidence: 99%